Assessing groundwater quality in peri-urban localities of Kumasi, Ghana. Issue 4 (2nd October 2019) - Aboagye, Dacosta; Zume, Joseph T.
ABSTRACT: This study examined groundwater quality in nine peri-urban communities of Kumasi, Ghana. These communities rely heavily on groundwater for domestic consumption amidst various sanitation concerns. The potential for groundwater contamination is high. Our study involved: (1) in-situ examination of physico-chemical characteristics of well water (2) laboratory analyses of groundwater samples for bacteria and heavy metals; (3) questionnaire surveys to obtain water use demographics. Results indicate groundwater contamination in all study communities. The questionnaire survey also reveal that the majority households in the communities consume their groundwater untreated. Thus, the study communities may be vulnerable to water-borne diseases.